POLYMORPHISM VITAMIN D RECEPTOR GENE (VDR) BSMI (RS1544410) CHRONIC PERIODONTITIS PATIENT IN JAVANESE BANYUMAS ETHNIC - Purnama, Ryana Budi; Logamarta, Setiadi Warata; Dhartono, Agung (Journal of Vocational Health Studies, 2021)
Background: Chronic periodontitis, a chronic inflammatory condition of periodontal tissue, can occur due to microorganisms as a local factor and genetic as a systemic factor. Genetic factors that cause chronic periodontitis, namely mutations in the form of a gene that functions to regulate calcium homeostasis, which is called the vitamin D receptor (VDR) gene. Mutated VDR gene causing different effect in a population and ethnic groups, including Javanese Banyumas Ethnic. Purpose: To understand the genotype distribution and VDR BsmI (rs1544410) gene allotype frequency chronic periodontitis patient in Javanese Banyumas Ethnic.  Method: The research was descriptive research in the form of a cross-sectional study of 26 chronic periodontitis patients in the Javanese Banyumas tribe. The samples obtained were carried out by the process of DNA isolation, Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP), and data in the Hardy-Weinberg Equilibrium (HWE) Court Lab analysis. Result: Whole samples from DNA isolation amplificated with one ribbon 524 bp VDR gene. RFLP restriction enzyme Bsml process is also showing cutting in each sample. From data analysis, X2 is 0,44 with p=0,50 (p>0,05) resulted. It was showing mutant VDR gene allele frequency in chronic periodontitis patients in Javanese Banyumas ethnic were balanced genetically. Conclusion: Genotype distribution in chronic periodontitis patient in Javanese Banyumas ethnic were 20 (76,9%) GG (bb) genotype, 6 (23,1%) GA (Bb) genotype, and 0 (0%) AA (BB) genotype with alel G (b) (wild type) allele frequency 0,88 (88%) and A allele (B or mutant) 0,12 (12%).